HUBUNGAN MOTIVASI BELAJAR DENGAN PRESTASI BELAJAR MAHASISWA PADA MATA KULIAH KEPERAWATAN ANAK AKADEMI KESEHATAN PROVINSI RIAU - , YULIANTO, Prof. dr. Djaswadi Dasuki, MPH, SpOG(K), Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: In the last 20 years the number of drop-out nursing students has been increasing by 20% . Student motivation to learn is generally regarded as one of the most important determinants of the success and quality of learning outcomes. According to the United Nations Development Programme (UNDP) Indonesia ranked 124 of 187 countries in the composition of educational attainment in 2011. Based on the data from Health Academy of Riau Province in the past two years, there is a decline in learning achievement in the subject of pediatric nursing, proven by its score achieved by students that those who scored a B in 2011 were 25,3% down to 13,7% in 2012, while score a C attained by students showed a significant decrease from 74% in 2011 to 84,3 % in 2012 . Objective: To determine the relationship between motivation to learn and student achievement in the subject of pediatric nursing in Health Academy of Riau Province. Methods: This was a study with a cross-sectional design. The study population was the second year students of Health Academy of Riau Province amounted to 52 people. Sampling technique used total sampling. The independent variabel was motivation to learn, the dependent variabel was student achievement in the subject of pediatric nursing and the extraneous variabels were student attitude, parental socioeconomy, maternal education and father's education. Data analysis consisted of univariabel analysis, bivariabel analysis using chi-square test and multivariabel analysis using logistic regression test with a significance level of p < 0,05 and 95% confidence interval. Results: There was a significant relationship between learning motivation and student achievement in the subject of pediatric nursing in Health Academy of Riau Province ( 2 = 20.56, p = 0,000) with RP = 7.46